Missed opportunities for immunization among children 0 to 11 months of age that were attended to at debre tabor comprehensive specialized hospital, south gondar zone, Ethiopia - Kassa, Bekalu Getnet; Lul, Nhial Char (Frontiers in Pediatrics, 2023)
Background: The World Health Organization's Expanded Immunization Program was established in 1974, and aimed to provide vaccines to children all over the world. Since the inception of this program, numerous initiatives and campaigns have been launched, and millions of children around the world have been saved from death. Many vaccine-preventable diseases, however, remain prevalent in developing countries. This is because most of those countries have low immunization coverage for an unknown number of reasons. As a result, the goal of this study was to examine missed opportunities for immunization among children aged 0-11 months. Methods: A cross-sectional survey was used from May to August 2022. A structured questionnaire was used to collect data, and the sample was chosen using a simple random sampling technique. Before being entered into Epidata and exported to Statistical Package for Social Science for analysis, the data were checked for consistency and completeness. The statistical significance was determined using binary and multiple logistic regression analyses. The statistical level of significance was established at p ≤ 0.05. Result: In this study, 49.1% of immunization opportunities were missed. Education status [AOR = 2.45, 95% CI = 2.14, 4.22], rural residence [AOR = 4.32, 95% CI = 3.11, 6.38], and perception of caretakers [AOR = 2.13, 95% CI = 1.89, 4.07] were associated with the missed opportunity of immunization. Conclusion: When compared to previous studies, the proportion of missed immunization opportunities was high in this study. The health care staff should be apply multi-dose vial policy, which recommend by World Health Organization to increase the services. The doses of BCG and measles should be minimized to lower doses per vial in order to conduct immunization without having to wait for enough children and without worrying about vaccine waste. All infants who visit the hospital should be linked to immunization services.